A review on strength exercise-induced muscle damage: applications, adaptation mechanisms and limitations - Brentano, M. A.; Martins Kruel, L. F. (The Journal of Sports Medicine and Physical Fitness, 2011)
This study aims to review the main aspects that induce muscle damage, and to discuss the adaptations of this phenomenon, applications and limitations of this study area. Damage induced by strength training has been utilized for two purposes: 1) verification of the recovery period required between training sessions, which has a direct influence on designing exercise programs; and 2) as indication for higher training intensity, mainly in studies on the "repeated bout effect". There is some speculation about the role of muscle damage in inducing hypertrophy. However, studies demonstrate that exercise-induced muscle damage may not be a consistent indicator of higher chronic hypertrophic response, because hypertrophy also occurs in training strategies with very low mechanical overloads. In addition, aerobic exercise, also induces muscle damage, exhibits no hypertrophic response after training. The remodeling process induced bay muscle damage promotes alterations to strength x length relationship for stretched positions, indicating an increased number of sarcomeres in series, due to strength exercises. Therefore, the study on strength exercise-induced damage seems to be adequate for implementing adequate rest periods to recovery from different sessions of strength training, and not to suggest chronic hypertrophy.